2020
DOI: 10.1186/s12951-020-00593-7
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of macrophage polarization by peptide-coated gold nanoparticles and its protective effects on acute lung injury

Abstract: Background: Macrophage polarization and reprogramming in the lung play a critical role in the initiation, development and progression of acute lung injury (ALI). Regulating the activation and differentiation of pulmonary macrophages may provide a potential therapeutic strategy to treat ALI. We previously developed a novel class of antiinflammatory nanoparticles (P12) that can potently inhibit Toll-like receptor (TLR) signaling in macrophages. These bioactive nanodevices were made of gold nanoparticles (GNPs) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 50 publications
2
95
0
Order By: Relevance
“…Many studies reveal an immunomodulatory role for NP (e.g., Au NPs, SiO 2 NP, functionalized polystyrene, and molybdenum disulfide quantum dots) that can drive macrophages polarization toward M1- or M2-like phenotypes ( 83 85 ). M1-like cells are classically activated inflammatory macrophages mainly involved in host defense to infections and tumors, while M2 defines alternatively activated macrophages mainly involved in type 2 inflammation, anti-inflammatory responses, wound-healing, tissue remodeling, and tumor growth ( 86 89 ).…”
Section: Nanoparticles and Cell Metabolismmentioning
confidence: 99%
“…Many studies reveal an immunomodulatory role for NP (e.g., Au NPs, SiO 2 NP, functionalized polystyrene, and molybdenum disulfide quantum dots) that can drive macrophages polarization toward M1- or M2-like phenotypes ( 83 85 ). M1-like cells are classically activated inflammatory macrophages mainly involved in host defense to infections and tumors, while M2 defines alternatively activated macrophages mainly involved in type 2 inflammation, anti-inflammatory responses, wound-healing, tissue remodeling, and tumor growth ( 86 89 ).…”
Section: Nanoparticles and Cell Metabolismmentioning
confidence: 99%
“…Activation and polarization of macrophages play a major role in the initiation and intensity of inflammation, respectively, in ALI/ARDS. Peptide-coated gold nanoparticles could alleviate lung inflammation through inducing M1-to-M2 macrophage phenotype transition and increasing the anti-inflammatory cytokine (IL-10) in the lung of acute lung injury (ALI) mice [71].…”
Section: Nanomedicinementioning
confidence: 99%
“…This approach may tune the inhibition of TLR4. Another study revealed that nanohybrids induced the polarization of alveolar M2 macrophages, but reduced M1 macrophages in an acute lung injury model [ 133 ].…”
Section: Nanoparticles For Anti-inflammation Therapymentioning
confidence: 99%